Adhesion enhancement strategy for Parylene C substrate by nanograss technique. (1st April 2022) - Chen, Lang; Xu, Han; Li, Tingyu; Zhang, Meixuan; Han, Xiao; Jin, Yufeng; Wang, Wei
Abstract: Parylene C is a commonly used polymer in the micro-electromechanical systems (MEMS) field because of its excellent barrier property and process compatibility with other microfabrications. Whereas, the poor adhesion of other materials to Parylene C is the urgent challenge that restricts its real applications. This work proposed a strategy to enhance the adhesion between Parylene C or metals and the Parylene C substrate. A short-time oxygen plasma reaction ion etching process with ambient titanium in the etching chamber is introduced between the first layer of Parylene C film deposition (the substrate) and the second Parylene C or metal coatings. Parylene C nanostructures (nanograss) are generated on the substrate because of the oxygen plasma bombarding with sputtered titanium nanoparticles as nanomasks. Different feature sizes of nanograss were successfully obtained by tuning the RF power, oxygen flow rate and etching times. Scanning electron microscopy images showed that both the nanograss density and height (0.61 ± 0.02 μ m–0.76 ± 0.03 μ m) were positively proportional to the etching time with low RF power (150 W) and oxygen flowrates (60 sscm). Scratch tests are conducted after the second layer of Parylene C or metal coatings to quantitively analyze the adhesion enhancement. The results indicated that the adhesion of both Parylene C and metal on the Parylene C substrate with nanograss structures were enhanced up to around 7 and 15 times, respectively, compared to those on untreated substrates. This nanograss technique-based adhesion enhancement approach is easy-to-realize, robust, chemical-free, precisely controllable, thereby holds promising potentials in various Parylene MEMS applications.